ANALISIS KINERJA KEUANGAN DITINJAU DARI RASIO LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS DI PT. POS INDONESIA (PERSERO) JAKARTA BARAT - Widodo, Wahyu; Komarudin, Mamay; Munawaroh, Munawaroh (STAI Darul Qalam Tangerang, 2024)
This study aims to determine the financial performance of PT. Pos Indonesia (Persero) West Jakarta from 2013-2015 in terms of liquidity, solvency, and profitability ratios. The method used in this study is qualitative descriptive research method. Qualitative descriptive research interprets and narrates data related to the situation that occurs. The results of the study are seen from the analysis of liquidity, solvency, and profitability ratios in 2013 the level of financial performance of PT. Pos Indonesia (Persero) West Jakarta is 146.08% which means it is very healthy because the final value according to the Decree of the Minister of Finance of the Republic of Indonesia No.826 / KMK.013 / 1992 is above 110%. This is due to the company's ability to generate increased profits. In 2014, the level of financial performance of PT. Pos Indonesia (Persero) West Jakarta is 65.45% which means it is unhealthy because the final value according to the Decree of the Minister of Finance of the Republic of Indonesia No.826 / KMK.013 / 1992 is below 90%. This is due to the company's ability to generate profits decreased, and due to the company's liquidity level being over-liquid. In 2015, the level of financial performance of PT. Pos Indonesia (Persero) West Jakarta is 159.72% which means it is very healthy because the final value according to the Decree of the Minister of Finance of the Republic of Indonesia No.826 / KMK.013 / 1992 is above 110%. This is due to the company's ability to generate increased profits, due to large revenue results compared to the costs incurred. The conclusion of this study is the overall financial performance of PT. Pos Indonesia (Persero) West Jakarta showed good performance. In order for financial performance to be even better, companies must further increase profits and reduce debt